2011
DOI: 10.2514/1.j050720
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Flow Properties of Supersonic Helium-Air Jets

Abstract: Heated high speed subsonic and supersonic jets operating on-or off-design are a source of noise that is not yet fully understood. Helium-air mixtures can be used in the correct ratio to simulate the total temperature ratio of heated air jets and hence have the potential to provide inexpensive and reliable flow and acoustic measurements. This study presents a combination of flow measurements of helium-air high speed jets and numerical simulations of similar helium-air mixture and heated air jets. Jets issuing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Doty and McLaughlin [24] and Papamoschou [25] have shown that mixtures of helium and air can appropriately simulate the noise of heated jets to a reasonable accuracy. Miller and Veltin [26] showed a good agreement of the mean flow properties between experimental data from helium-air mixture jets and a numerical calculation of heated air jets. Recent careful comparisons [27] between the measurements conducted at Pennsylvania State University with the measurements performed in other facilities have shown very good agreement when matching the acoustic velocity of the helium-air mixture jet to that of a heated jet following a procedure developed by Doty and McLaughlin [24] over 10 years ago.…”
Section: A Facility and Instrumentation Descriptionsmentioning
confidence: 68%
“…Doty and McLaughlin [24] and Papamoschou [25] have shown that mixtures of helium and air can appropriately simulate the noise of heated jets to a reasonable accuracy. Miller and Veltin [26] showed a good agreement of the mean flow properties between experimental data from helium-air mixture jets and a numerical calculation of heated air jets. Recent careful comparisons [27] between the measurements conducted at Pennsylvania State University with the measurements performed in other facilities have shown very good agreement when matching the acoustic velocity of the helium-air mixture jet to that of a heated jet following a procedure developed by Doty and McLaughlin [24] over 10 years ago.…”
Section: A Facility and Instrumentation Descriptionsmentioning
confidence: 68%
“…20 Kinzie and McLaughlin 21 and Papamoschou 22 have shown that mixtures of helium and air can appropriately replicate the aeroacoustics of heated jets to a reasonable accuracy by matching the acoustic velocity of the heated gas. Miller and Veltin 23 showed a good agreement of the flow properties between the experimental data from helium-air mixture jets and the numerical RANS calculations of heated air jets. Additionally, a comparison between experimental data from the laboratory helium-air jets in the High Speed Jet Aeroacoustics Facility at Penn State and the moderate-scale heated jet noise facility at NASA GRC was made.…”
Section: Technical Approach Facility Description and Overviewmentioning
confidence: 64%
“…The mixture’s total pressure is controlled to within 5% of the target value during data acquisition. This methodology, developed by Kinzie 35 and Doty and McLaughlin, 36 has been demonstrated to accurately replicate the noise 37 and velocity profiles 38 of heated air jets. A comparison between experimental data from model-scale heat-simulated jets in the high-speed jet aeroacoustics facility at Penn State and the moderate-scale heated jet noise facility at NASA Glenn Research Center, which show excellent agreement, can be found in McLaughlin et al 39…”
Section: Experimental Approachmentioning
confidence: 99%